2022
DOI: 10.36560/15320221522
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade e câncer: mecanismos envolvidos e intervenções terapêuticas

Abstract: A transição demográfica iniciada no Brasil, a partir da década de 60, promoveu mudanças nos hábitos de vida da população, promovendo alterações no perfil nutricional e nas manifestações de doenças. No início do século XXI, ocorreu um marco no qual, pela primeira vez, o número de indivíduos com excesso de peso ultrapassou os de baixo peso, o que é preocupante, pois a obesidade é apontada como um dos principais fatores de risco para inúmeras patologias crônicas, incluindo diabetes, dislipidemia, doenças cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…BMI is used worldwide as an indicator of body weight and as an index to diagnose overweight and obesity, thereby assessing the risk of developing other diseases, such as CRC. 15,[32][33][34] The present study observed that the majority of patients diagnosed with CRC had a BMI ≥ 25 kg/m 2 (68.3%).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…BMI is used worldwide as an indicator of body weight and as an index to diagnose overweight and obesity, thereby assessing the risk of developing other diseases, such as CRC. 15,[32][33][34] The present study observed that the majority of patients diagnosed with CRC had a BMI ≥ 25 kg/m 2 (68.3%).…”
Section: Discussionsupporting
confidence: 47%
“…[10][11][12] Hyperinsulinemia can promote proliferation and inhibit apoptotic mechanisms in cancer cells. [13][14][15] Additionally, in chronic lowgrade inflammation, unbalanced levels of cytokines with increased levels of proinflammatory adipokines and decreased levels of antiinflammatory adipokines are observed, 5, 15 which can contribute to tumor development. 16 Maintaining healthy eating habits, with a balanced diet rich in fruits and vegetables and a low intake of processed foods, foods rich in carbohydrates and fats, and red meats, contributes to preventing the development of overweight and obesity as well as cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is associated with several diseases, being a risk factor for the development of other comorbidities that include glucose intolerance, dyslipidemia, hepatic steatosis, nonalcoholic fatty liver disease, diabetes, cardiovascular diseases, depression, and cancer 4–8 . This metabolic and multifactorial disease is the result of complex polygenic factors and an obesogenic environment 1–3,9 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Obesity is associated with several diseases, being a risk factor for the development of other comorbidities that include glucose intolerance, dyslipidemia, hepatic steatosis, nonalcoholic fatty liver disease, diabetes, cardiovascular diseases, depression, and cancer. [4][5][6][7][8] This metabolic and multifactorial disease is the result of complex polygenic factors and an obesogenic environment. [1][2][3]9 Changes in eating behavior, as well as sedentary lifestyle habits, act on susceptible genes that are believed to be the main drivers for the worldwide increase in obesity among people.…”
mentioning
confidence: 99%